2007
DOI: 10.1103/physrevlett.99.097201
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Gapped Spin-Wave Excitations in the FrustratedGd2Sn2O7Pyrochlore Antiferromagnet from Low-Temperature Specific Heat Measurements

Abstract: We have measured the low-temperature specific heat of the geometrically frustrated pyrochlore Heisenberg antiferromagnet Gd2Sn2O7 in zero magnetic field. The specific heat is found to drop exponentially below approximately 350 mK. This provides evidence for a gapped spin-wave spectrum due to an anisotropy resulting from single ion effects and long-range dipolar interactions. The data are well fitted by linear spin-wave theory, ruling out unconventional low-energy magnetic excitations in this system, and allowi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 28 publications
7
42
0
Order By: Relevance
“…The different magnetic structures and the ordering processes between GTO and GSO are also echoed by their distinct low-energy spin excitations below T N . The magnetic specific heat C m (T) of GSO drops exponentially below 350 mK, 11 pointing to a conventional, gapped spin-wave excitations, which was confirmed by the inelastic neutron scattering. 15 Starting from the P-C state, Del Maestro and Gingras 27 actually predicted such conventional magnons gapped by the single-ion anisotropy and dipolar interactions.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…The different magnetic structures and the ordering processes between GTO and GSO are also echoed by their distinct low-energy spin excitations below T N . The magnetic specific heat C m (T) of GSO drops exponentially below 350 mK, 11 pointing to a conventional, gapped spin-wave excitations, which was confirmed by the inelastic neutron scattering. 15 Starting from the P-C state, Del Maestro and Gingras 27 actually predicted such conventional magnons gapped by the single-ion anisotropy and dipolar interactions.…”
Section: Introductionmentioning
confidence: 75%
“…40 Another noteworthy feature in Fig. 4(a) is that the drop of C(T) for GGO and GPO at the lowest temperature region is less profound as GSO 11 , implying the presence of different low-energy magnetic excitations.…”
Section: Specific Heatmentioning
confidence: 97%
See 2 more Smart Citations
“…In Gd 2 Sn 2 O 7 , a first-order transition to an ordered state occurs at T N = 1.0 K (≈ θ CW /10) [17], and neutrondiffraction measurements have shown that this is indeed the Palmer-Chalker state [18,19]. Recently, debate has focussed on the possible presence of spin fluctuations at temperatures much lower than T N [14,20,21,22]. Much less attention has been given to the paramagnetic phase; however, it is known to be strongly correlated, with approximately 60% of the total magnetic entropy associated with the development of short-range correlations above T N [17].…”
Section: Introductionmentioning
confidence: 99%